Rare case of bizarre leiomyoma in Mayer-Rokitansky-Küster-Hauser Syndrome - F.Q. Sun; T. Wang; X.H. Xu; C. Han; J. Jin (IMR Press, 2020)
The authors report a case of leiomyoma that developed from an aplastic uterus in a 38-year-old Chinese female with a typical Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome. She had normal female secondary sexual characteristics, normal external genitalia with discernible vagina, primary amenorrhea, and infertility with asymptomatic a left adnexal mass. Pelvic MRI showed a mass of 3.7 cm in the left pelvis and a mass of 1.5 × 1.4 × 2.6 cm3 in the right pelvis without a normal functioning uterus and vagina between the bladder and rectum. Laparoscopic exploration showed that the bilateral rudimentary uteri located laterally in the pelvis and they had a constant caudal relationship with their paired ovary. The bilateral fallopian tubes and ovaries were normal. A leiomyoma developed from the left rudimentary uteri. Removal of the left leiomyoma, bilateral rudimentary uteri and fallopian tubes was performed with preservation of bilateral ovaries. The histologic diagnosis showed that the bilateral rudimentary uteri had no clear structures of uterine cavity and endometrium, and the bizarre leiomyoma developed from the left rudimentary uterus without necrosis or mitosis.